2011
DOI: 10.1510/icvts.2011.272914
|View full text |Cite
|
Sign up to set email alerts
|

Complete transposition of carotid bifurcation: can it be an additional risk factor of injury to the cranial nerves during carotid endarterectomy?

Abstract: The internal carotid artery (ICA) usually, lies posterolaterally to the external carotid artery (ECA). Sometimes a complete carotid transposition can occur, with the ECA in a lateral position and the ICA on the medial side can occur. Our study evaluated the significance and impact that this anomaly may have on cranial nerve injuries. From January 2008 to November 2010, 296 patients underwent 360 consecutive primary carotid endarterectomy (CEA) procedures. During carotid isolation, we detected an unexpected lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 17 publications
1
30
1
Order By: Relevance
“…[3,4,7,10] is anomaly was also called "side-by-side carotid artery, " "dorsal/dorsomedial origin of the ICA, " or "lateral ECA. " [5,[12][13][14][15][16]20] Although several series and/or cases have been reported, we clarified the frequency and other clinical features of the twisted ICAs among our CEA-treated cases and…”
Section: Introductionmentioning
confidence: 99%
“…[3,4,7,10] is anomaly was also called "side-by-side carotid artery, " "dorsal/dorsomedial origin of the ICA, " or "lateral ECA. " [5,[12][13][14][15][16]20] Although several series and/or cases have been reported, we clarified the frequency and other clinical features of the twisted ICAs among our CEA-treated cases and…”
Section: Introductionmentioning
confidence: 99%
“… 4) However, the anatomical relationships between the ECA and ICA of patients scheduled to undergo CEA have never been evaluated by CCE. 5) …”
Section: Discussionmentioning
confidence: 99%
“…Angiography findings have shown that the incidence of TCB or LPECA in various diseases is 4.3%-4.9% in Japanese populations 10,12) and 3.6%-15.1% during CEA. [5][6][7][8]10,14,15) Therefore, this abnormality is actually quite prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations